A PROMISING APPROACH TO DEVELOP MAIZE IN BREDS AND TEST THEIR HYBRID PERFORMANCE - & et al., Elsahookie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A project to develop new maize (Zea mays L.) inbreds from inbred populations, crossed, and tested for performance. The project elapsed six seasons, 3 spring and 3 full plantings during 2015-2017. Newly developed inbreds showed significant grain yield increase as compared to the cross of its progenitor inbred. An increase of 2 t ha-1 was obtained with one of the new inbreds. The crosses obtained were evaluated in field trials with a registered hybrid (60×21). Method of selection counts on a unique plant trait in the inbred population, such as longer ear, thicker ear diameter, stay-green leaves, large kernel, and so on. The merit obtained due to hybrid vigor could be attributed to parental inbreds that have high number of SSR, genetically diverse loci or DNA methylation. The check hybrid (60×21) produced an average of 9.0 t ha-1. Meanwhile, the cross 60×73 produced 9.01 t ha-1, while the two newly derived inbreds produced higher grain yields, 60×73fr and 60×73dr which exceeded 11.0 t ha-1. We have represented the case of hybrid vigor in a mathematical form; +1